Integrated humidity sensor based on SU-8 polymer microdisk microresonator - (:unkn) unknown (ELSEVIER SCIENCE SA, 2017)
Due to its high interaction with water vapor and photolithographic patterning property, SU-8 is a favorable hygroscopic polymer for developing humidity sensors. In addition, optical resonances of optical microresonators are very sensitive to the dianges in their environment. Here, we present integrated optical humidity sensors based on chips containing SU-8 polymer microdisks and waveguides fabricated by single-step UV photolithography. The performance of these sensors is tested under a wide range of relative humidity (RH) levels (0-50%). A tunable laser light is coupled from an excitation fiber to individual SU-8 waveguides using end-face coupling method. As the laser wavelength is scanned, the whispering gallery modes (WGMs) are revealed as dips in the transmission spectra. Sensing is achieved by recording spectral shifts of the WGMs of the microdisk microresonators. Red shift is observed in the WGMs with increasing RH. Between 0 and 1% RH, an average spectral shift sensitivity of 108 pm/% RH is demonstrated from measurements performed on 4 sensor devices. This sensitivity is comparable to the highest values obtained using microresonators in the literature. Measurements performed with another sensor device revealed a decrease in sensitivity by only around 3 times when RH is increased to 45-50%. Finite element modeling simulations are carried out to determine the dominant effect responsible for the resonance shift. The results show that the refractive index change is more important than the microresonator size change. The standard deviation in wavelength measurement is <3 pm, indicating a limit of detection better than 0.03% RH. These results suggest that optical sensor devices that contain integrated SU-8 microresonators and waveguides can be employed as easy-to-fabricate and sensitive humidity sensors. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Microdisk; Whispering gallery mode; SU-8; FEM; humidity sensor; microresonator; FABRICATION